2010
DOI: 10.1155/2010/251621
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter Arterial Chemoembolization Is a Feasible Palliative Locoregional Therapy for Breast Cancer Liver Metastases

Abstract: Background. Liver metastases are common in advanced breast cancer. We sought to evaluate the role of transcatheter arterial chemoembolization (TACE) in breast cancer patients with hepatic metastases. Methods. A retrospective review of ten patients with breast cancer who were treated with TACE for unresectable liver metastases (1998–2008). Results. All patients, median age 46.5, had received prior systemic chemotherapies. Adriamycin was administered for 6, cisplatin/gemcitabine for 2, cisplatin for one and oxal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 22 publications
0
17
0
4
Order By: Relevance
“…For example, in TACE, which uses vessel embolization to induce cancer tissue necrosis, surrounding tissue is also obliterated [30]. Furthermore, any remaining embolization- or radiotherapy-resistant cancer tissue tends to be more malignant and can lead to metastasis [55, 56].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in TACE, which uses vessel embolization to induce cancer tissue necrosis, surrounding tissue is also obliterated [30]. Furthermore, any remaining embolization- or radiotherapy-resistant cancer tissue tends to be more malignant and can lead to metastasis [55, 56].…”
Section: Resultsmentioning
confidence: 99%
“…However, these therapies not only affect solid tumors but also normal cells, which is an area of concern in cancer treatment [27]. Furthermore, cancer therapies, such as transarterial chemoembolization (TACE) that uses blood vessels may not produce the desired results, and this may even increase vascular proliferation and growth into a malignant tumor by incomplete responses [30]. A correlation between hypoxia, cancer proliferation, and angiogenesis and the mechanism of growth or development of tumors has been observed [31].…”
Section: Introductionmentioning
confidence: 99%
“…Though TACE may theoretically offer escalated local dosing or combinations of chemotherapeutics, therapeutic failure rates are high with PD in 51-60% of patients (42,43) even when multiple cytotoxic agents and dose selection are tailored to individual mBC patients based on their history of systemic treatment (43). Buijs et al reported 26% of treated lesions had partial RECIST response after multi-agent TACE yet 0 of 14 patients had a net partial response based on total tumor burden and the number of patients with stable or PD and toxicity were not specified (40).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, direct liver delivery may result in a better systemic toxicity profile. The chemotherapeutic effect of TACE on tumor cells is also increased by embolization-induced tumor ischemia [49]. Published data suggest that TACE may have a palliative role in delaying progression of isolated LiM.…”
Section: Local Treatment Of Selected Disease Sitesmentioning
confidence: 99%